درجة كفاءة برنامج التربية الميدانية لطالبات كلية التربية في جامعة حائل من وجهة نظر الطالبة / المعلمة - خصاونة، خلود أحمد سليم (جامعة القدس المفتوحة, 2014)
تهدف هذه الدراسة إلى تقويم كفاءة برنامج التربية الميدانية في جامعة حائل من وجهة نظر الطالبة /المعلمة. كما تهدف إلى تقصي أثر متغير المعدل التراكمي للطالبة على تقويمها لمجالات برنامج التربية الميدانية. وتألفت عينة الدراسة من (186) طالبة تم اختيارهن بالطريقة القصدية. وكانت أداة الدراسة المستخدمة استبانة تكونت من ( 61 ) فقرة، تم التحقق من صدقها وثباتها. وأظهرت النتائج أن تقويم الطالبات لكفاءة برنامج التربية الميدانية كان على النحو الآتي : احتل مجال تقويم مشرفة التربية الميدانية المرتبة الأولى، فالمعلمة المتعاونة، ثم إجراءات برنامج التربية الميدانية، فالمدرسة المتعاونة، وأخيرا مديرة المدرسة المتعاونة. وأظهرت النتائج عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.05 ≥ ) في تقويم الطالبات / المعلمات لكفاءة برنامج التربية الميدانية تعزى إلى المعدل التراكمي. This study aimed at detecting the degree of the efficiency of Practicum Program in the Faculty of Education Department as represented by the educational supervisor, the cooperative teacher, the school principal, the cooperative school, and the procedures applied in the Practicum program. It also aimed at identifying the effect of the variables of the student' s GPA on .his/her evaluation of the Practicum Program The sample of the study consisted of (186) female students who were chosen in an intended way. The instrument of the study was a questionnaire .that consisted of (61) items whose reliability and validity was verified. The results showed that the domains of the evaluation of the Practicum ,were ranked as followed: supervisor domain, the cooperative teacher domain the procedures domain, the cooperative school domain, and the cooperative school principal domain respectively. The results also revealed that there are no significant statistical differences at ( ≥ 0.05) in the students/teacher evaluation of the Practicum Program due to the teacher/ student students GPA
Keywords: التربية الميدانية -- درجة الكفاءة